The carriers of Vilamovian identity and their revitalization - Hołodewicz, Olga (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
The article lists and briefly characterizes the elements of Vilamovian culture and tradition that are most essential to their ethnic identity and sense of cultural difference. These are, first and foremost, the Wymysorys (Vilamovian) language, which is currently in danger of extinction, and the traditional women’s attire. The article also references belles-lettres, or fine literature, written in the Vilamovian language, emphasizing that it is not widely known among the town’s residents, and is not an important carrier of local identity in comparison to language and attire. The text further details the issue of the persecution of the Vilamovian culture under the communist rule in Poland, and the dynamics of the language revitalization processes after the fall of communism in 1989.